La desmitificación de árabes y musulmanes a través de la teledramaturgia brasileña: un estudio de la telenovela "O Clon": The demystification of Arabs and Muslims through Brazilian teledramaturgy: a study of the telenovela "The Clone" - Balbino, Jéfferson (Caminhos da História, 2022)
Reseña del libro: PORTO, César Henrique de Queiroz. A Representação dos árabes e muçulmanos na televisão brasileira. 1. ed. Curitiba: Appris, 2020.